The Effect of Purple Yam (Dioscorea alata) and Crookneck pumpkin (Cucurbita moschata) Substitution on Organoleptic and Chemical Properties of Dodol - Danna Oksadilla; Rachmawati Rachmawati; Dini Junita (JAND: Journal of Applied Nutrition and Dietetic, 2022)
Dodol is a semi-wet food made from glutinous rice flour, coconut milk, and sugar, occasionally added with permitted food ingredients and other food additives. Purple yam and crookneck pumpkin can be added to dodol to change it. The objective is to determine how the substitution of purple yam and crookneck pumpkin may affect the chemical and organoleptic characteristics of dodol. The panelists used in this study were semi-panelists. This type of research is experimental with a completely randomized design (CRD), specifically 3 treatments and 3 repetitions using the hedonic test. Up to 30 students were trained, originating from the Department of Nutrition, Ministry of Health, Aceh. Utilizing the ANOVA (Analysis of Variance) and Duncan's New Multiple Range tests, data processing and analysis were performed. The most liked dodol is dodol with the addition of 80 g of purple yam and 40 g of crookneck pumpkin. Dodol organoleptic test results include taste, aroma, texture, and color. The proximate test findings demonstrated that the addition of 40g of crookneck pumpkin and 80g of purple yam had an impact on the levels of fat and carbohydrates, and had a significant impact on the color, taste, aroma, and texture. It also had a significant impact on the proximate test of the food's fat and carbohydrate content. According to the researcher's recommendations, the dodol should be cooked for a longer period and with more glutinous rice flour in order to reduce its water content and extend its shelf life.